The Influence of Consumer Animosity, Boycott Participation, Boycott Motivation, and Product Judgment on Purchase Readiness or Aversion in Pizza Hut in Indonesia - Banjaransari, Harimurti (Syntax Literate, 2025)
This study aims to analyze the effects of consumer animosity, boycott participation, boycott motivation, and product judgment on purchase readiness and purchase aversion toward Pizza Hut products in Indonesia. The research background stems from the high sensitivity of the Indonesian public to the Israel-Palestine conflict, which has sparked boycotts against companies perceived as supporting Israel. The study adopts a quantitative approach, with data collected via online questionnaire surveys targeting Pizza Hut consumers in Indonesia. The sample includes Indonesian citizens aged at least 17 years, residing in Indonesia, who have purchased Pizza Hut products within the last two years and are aware of boycott campaigns against the Pizza Hut brand. The collected data were analyzed using the Structural Equation Modelling (SEM) method with SmartPLS 3.0. The findings reveal that consumer animosity has a significant positive effect on boycott participation and boycott motivation. However, it does not directly influence purchase readiness.